2018
DOI: 10.1016/j.margeo.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of flocculation dynamics under changing hydrodynamic forcing on an intertidal mudflat

Abstract: In situ floc size and turbulent shear stress were measured together with suspended sediment concentration to investigate the floc properties under changing hydrodynamic forcing over the intertidal mudflat. A tripod system was established in the field for a period of approximately one month, including~6 days of stormy conditions in the middle of the investigation period. Mean floc size exhibited strong temporal variations within a tidal cycle, and inverse relationship was found between mean floc size and shear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…Typical values were found to be 4 cm during calm conditions and about 13 cm during strong winds (6 Bft). The sediment on the flat is cohesive, with a median grain size less than 50 μm (Guo et al, ; Zhu, ). The suspended sediment concentration in the channels of the estuary fluctuates strongly in space and time, around an average of about 40 mg/L (van der Wal et al, ).…”
Section: Study Area and Field Datamentioning
confidence: 99%
“…Typical values were found to be 4 cm during calm conditions and about 13 cm during strong winds (6 Bft). The sediment on the flat is cohesive, with a median grain size less than 50 μm (Guo et al, ; Zhu, ). The suspended sediment concentration in the channels of the estuary fluctuates strongly in space and time, around an average of about 40 mg/L (van der Wal et al, ).…”
Section: Study Area and Field Datamentioning
confidence: 99%
“…The reason for the added complexity is that cohesive particles can create aggregates, called flocs, which are orders of magnitude larger than the primary constituent grains of the aggregate (van Leussen, ; Figure ). Furthermore, the flocs can grow or shrink in size depending on environmental conditions such as sediment mineralogy, water column chemistry and organic content, suspended sediment concentration, turbulent shear stress, and floc shape (Dyer, ; Guo et al, ; Krone, ; Partheniades, ; Tang et al, ; Winterwerp & van Kesteren, ). In particular, sediment concentration, C (mass/vol), and the mean shear rate of turbulence, G (1/t or Hz; or turbulent shear rate), are often thought to be the key determiners of flocs size for a particular system with constant sediment type, biological content, and salinity.…”
Section: Introductionmentioning
confidence: 99%
“…Flocs are totally different from primary sediment particles in terms of their larger sizes, lower excess density, and higher settling velocity in water [2,6]. Studying cohesive sediment flocculation in a turbulent flow environment is essential because it plays an important role in affecting the morphological changes to coastal areas, dredging operations in navigational canals, and sediment siltation in reservoirs and 2 of 20 lakes [7,8]. Since some pollutants (such as heavy metals) and nutrients are absorbed on the surfaces of cohesive sediment particles due to the electrochemical attraction of clay particles and/or organic matter contained in the sediment, the flocculation of cohesive sediment is also a vital element in investigating the variation of water quality and ecosystem function in some waters such as lakes and estuarine and coastal waters, which contain an abundance of cohesive sediment [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Some experimental works have been performed to investigate the median value of the size distribution of the flocs at the steady state of flocculation with respect to various flow shear conditions (e.g., References [8,14,[24][25][26][27]. These studies reported that the median floc size decreases as the flow shear stress increases.…”
Section: Introductionmentioning
confidence: 99%